OPTICAL DEVICE, CONTROL METHOD FOR OPTICAL DEVICE, AND PROGRAM - ARAI MASATO; KIMOTO TATSUYA; HIGASHIYAMA TERUYUKI (2024)
To provide an optical device capable of acquiring high-density point cloud data at approximately equal intervals.SOLUTION: An optical device (100) includes a mirror (7) that irradiates an object (11) with light and guides reflected light (12) reflected by the object, a first motor (13) that rotates the mirror about a first axis, a second motor (14) that rotates the mirror about a second axis, and a control unit (15) that controls the first motor and the second motor. A center point (C) of a mirror surface of the mirror is positioned at a position different from the second axis, and a reflective optical axis surface of the mirror is not parallel to a plane including the second axis.SELECTED DRAWING: Figure 1 【課題】高密度な点群データをほぼ等間隔で取得することが可能な光学装置を提供する。【解決手段】光学装置（１００）は、対象物（１１）に光を照射して前記対象物で反射した反射光（１２）を導くミラー（７）と、第１軸の周りに前記ミラーを回転させる第１モータ（１３）と、第２軸の周りに前記ミラーを回転させる第２モータ（１４）と、第１モータおよび第２モータを制御する制御部（１５）とを有し、ミラーのミラー面の中心点（Ｃ）は、前記第２軸とは異なる位置に配置されており、ミラーの反射光軸面は、第２軸を含む平面と平行ではない。【選択図】図１